Realization of The Politeness Principles used by Atas Market and Bawah Market Muara Bungo Traders in Their Speech to The Buyer - Rini Afrilesa J (Fakultas Sastra Universitas Ekasakti, 2020)
This research is motivated by the utterances of traders in the Atas market and Bawah markets of Muara Bungo, which have a good politeness value. In this study, researchers used a qualitative descriptive approach in which data results were based on existing observations and interpretations. The data studied were the stories of traders recorded in the Atas and Bawah markets of Muara Bungo. After recording the data is transcribed and grouped based on the type of speaker. After that, the data will be analyzed in terms of compliance with and violations of the principles of decency according to Leech theory. The realization of courtesy of the Atas market traders and the Bawah markets in Muara Bungo both have a good politeness value. Through the author's observations, the Atas market traders are more friendly than the Bawah market.